Alkynylation of Aldehydes Initiated by Cathodic Reduction - Dr. Eisuke Sato; Mayu Fujii; Dr. Koichi Mitsudo; Prof. Dr. Seiji Suga (ChemElectroChem, 2024)
Abstract Alkynylation of aldehydes initiated by cathodic reduction was performed. The cathodic alkynylation required only a semi‐catalytic amount of electricity to consume the starting material completely. Cyclic voltammetry and some control experiments suggest that the electron‐generated base derived from the cathodic reduction of benzaldehyde promotes alkynylation.